Artificial oocyte activation with SrCl2 or calcimycin after ICSI improves clinical and embryological outcomes compared with ICSI alone: results of a randomized clinical trial. Issue 9 (7th August 2018) - Fawzy, Mohamed; Emad, Mai; Mahran, Ali; Sabry, Mohamed; Fetih, Ahmed N; Abdelghafar, Hazem; Rasheed, Salah
Abstract: STUDY QUESTION: Are pregnancy and birth rates affected by artificial oocyte activation (AOA) with SrCl2 or calcimycin after ICSI for couples with male-factor infertility linked to abnormal sperm morphology or for couples with previous ICSI cycles of unexplained low fertilization or inadequate fertilization associated with impaired oocyte morphology? SUMMARY ANSWER: AOA with either SrCl2 or calcimycin can improve the rates of clinical pregnancy, ongoing pregnancy and live birth compared with ICSI alone, and the two agents have diverse effects for different subgroups of patients. WHAT IS KNOWN ALREADY: ICSI is a successful treatment for infertility, but not in all individuals. AOA has potential to overcome inadequate fertilization in ICSI. Calcimycin and SrCl2 are candidate agents for AOA, but their effectiveness remains to be compared. STUDY DESIGN, SIZE, DURATION: This study was a randomized, open-label, three-arm, parallel-group, double-centre, superiority trial conducted between April 2015 and January 2016. The study evaluated the effects of AOA with calcimycin or SrCl2 for clinical pregnancy rates after ICSI and included 343 couples divided into three groups. PARTICIPANTS/MATERIALS, SETTING, METHODS: Couples were included if they had two previous ICSI cycles of no or low fertilization (0–30%) with unknown causes or impaired oocyte morphology. Male-factor infertility cycles (frozen–thawed sperm, surgically retrieved sperm or ejaculates contained <10 millions spermatozoa/ml) undergoing their first ICSI attempt were also included if they had 100% abnormal sperm morphology (including globozoospermia and tapered-head). Couples were randomized to undergo ICSI with SrCl2 AOA, ICSI with calcimycin AOA or ICSI alone, with clinical pregnancy as the primary endpoint. Effect sizes were summarized as absolute rate differences (ARDs) and odds ratios (ORs), with precision evaluated by 95% CIs. MAIN RESULTS AND THE ROLE OF CHANCE: Both SrCl2 and calcimycin AOA improved clinical pregnancy rates compared to ICSI alone (49, 42 and 27%; ARD 22, 95% CI: 9–33; P = 0.0007 and ARD 16, 95% CI: 3–27; P = 0.014). SrCl2 and calcimycin AOA were also superior to ICSI alone on the rates of ongoing pregnancy (42, 36 and 23%; P = 0.0019 and P = 0.023) and live birth (40, 33 and 18%; P = 0.0002 and P = 0.012). Among couples with previous ICSI cycles of low fertilization, AOA with SrCl2 (but not with calcimycin) was superior to ICSI alone for rates of clinical pregnancy (ARD 35 percentage points (pp), P = 0.0007), ongoing pregnancy (ARD 27 pp, P = 0.009) and live birth (ARD 37 pp, P = 0.002). Among couples affected by male-factor infertility, AOA with calcimycin (but not with SrCl2 ) was superior to ICSI alone for rates of clinical pregnancy (ARD 22 pp, P = 0.006), ongoing pregnancy (ARD 19 pp, P = 0.013) and live birth (ARD 17 pp, P = 0.02). LIMITATIONS, REASONS FOR CAUTION: This study was an open-label trial, and this design might have introduced bias, although randomization methods were used. The study did not include a longitudinal follow-up, so further evidence is required to demonstrate the safety of AOA. WIDER IMPLICATIONS OF THE FINDINGS: The decision to use SrCl2 or calcimycin for AOA after ICSI may depend on whether the activation failure originates in the oocyte or the sperm. STUDY FUNDING/COMPETING INTEREST(S): The study received no funding and the authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: NCT02424214. TRIAL REGISTRATION DATE: 22 April 2015. DATE OF FIRST PATIENT'S ENROLMENT: 27 April 2015.